2019
DOI: 10.3390/foods8050169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Gums on Textural and Microbial Properties of Goat Milk Yogurts during Refrigerated Storage

Abstract: In this study, the impact of seven different gums on textural and microbiological properties of goat milk yogurt during refrigerated storage was investigated. The results showed that yogurt containing xanthan and locust bean gums had enhanced firmness, consistency, cohesiveness, and viscosity during four weeks of storage compared to the control and yogurt fortified with other gums (p < 0.05). The addition of gums also helped to maintain the microbial viability of the yogurt culture and the probiotic Bifidob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…The data reported here for firmness ( Table 4 ) were in line with Costa et al [ 4 ], Park et al [ 67 ], and Miocinovic et al [ 68 ] for goat milk yogurts stored at 4 °C and unfortified with gums or protein isolate. Moreover, our results agree with Jalilzadeh et al [ 38 ], who reported no difference in hardness between US-treated and control cheese samples during 60 days of ripening.…”
Section: Discussionsupporting
confidence: 91%
“…The data reported here for firmness ( Table 4 ) were in line with Costa et al [ 4 ], Park et al [ 67 ], and Miocinovic et al [ 68 ] for goat milk yogurts stored at 4 °C and unfortified with gums or protein isolate. Moreover, our results agree with Jalilzadeh et al [ 38 ], who reported no difference in hardness between US-treated and control cheese samples during 60 days of ripening.…”
Section: Discussionsupporting
confidence: 91%
“…Porém, os valores de pH das formulações foram considerados adequados de acordo com a legislação vigente no Brasil para leites fermentos (Brasil, 2007). De acordo com Park et al (2019), o pH está relacionado à atividade metabólica das bactérias. Assim, durante o processo de fermentação do iogurte, microrganismos do gênero Lactobacillus multiplicam-se em pH mais baixos comparados aos do gênero Streptococcus.…”
Section: Resultsunclassified
“…This could be attributed to protein aggregates formed by the interaction via intermolecular disulphide bonds of casein micelles with denatured whey proteins. Park et al (2019) demonstrated that the water absorption capacity increased with the addition of carob bean gum. The authors stated that the xanthan and carob supplemented yogurt for the experimental goat yogurt showed significantly (p < 0.05) better consistency than the control and other gum added yogurts.…”
Section: Effect Of Carob Galactomannans On Viscosity Of Fermented Milksmentioning
confidence: 99%